2010
DOI: 10.1158/1078-0432.ccr-10-0791
|View full text |Cite
|
Sign up to set email alerts
|

A Phase I Study of a Tropism-Modified Conditionally Replicative Adenovirus for Recurrent Malignant Gynecologic Diseases

Abstract: Purpose: To determine the maximum tolerated dose (MTD), toxicity spectrum, clinical activity, and biological effects of the tropism-modified, infectivity-enhanced conditionally replicative adenovirus (CRAd), Ad5-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
68
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(74 citation statements)
references
References 25 publications
(26 reference statements)
3
68
0
Order By: Relevance
“…This increases the antitumor potential and efficacy of nanocarriers, since they decrease the nutrients and oxygen delivery to the tumors, and release the low molecular anticancer drugs in the vicinity of the tumor vasculature [49,85]. This promising strategy is under preclinical development, with a few clinical examples in phase I [87][88][89]. An additional drawback, that contributes to the current clinical failure of active targeting nanocarriers, comprises the increased immunogenicity and plasma protein adsorption when targeting moieties are included in the nanocarriers, decreasing their bloodstream circulation time and their ability to passively target the tumors [85].…”
Section: Reprinted By Permission From Macmillan Publishers Ltd: [Natumentioning
confidence: 99%
“…This increases the antitumor potential and efficacy of nanocarriers, since they decrease the nutrients and oxygen delivery to the tumors, and release the low molecular anticancer drugs in the vicinity of the tumor vasculature [49,85]. This promising strategy is under preclinical development, with a few clinical examples in phase I [87][88][89]. An additional drawback, that contributes to the current clinical failure of active targeting nanocarriers, comprises the increased immunogenicity and plasma protein adsorption when targeting moieties are included in the nanocarriers, decreasing their bloodstream circulation time and their ability to passively target the tumors [85].…”
Section: Reprinted By Permission From Macmillan Publishers Ltd: [Natumentioning
confidence: 99%
“…ONYX-015, H101 (Oncorine) and other first-generation oncolytic crHAdVs have gone through several phase I/II trials without relevant signs of high grade toxicity but also without significant therapeutic effects, resulting in discontinuation of further trails. 48 More recent clinical trials employing new generations of crHAdVs like RGD retargeted oncolytic crHAdVs, 20,49,50 crHAdV-5/3 chimeric vectors, 32,[51][52][53][54] ColoAd1, 55 hTERT-promoter driven crHAdV-5 vector Telomelysin, 56 E2F-1-promoter driven CG0070 33 , Rbtargeted crHAdV expressing hyaluronidase (VCN-01) 57 and crHAdV vectors expressing immunomodulating genes have shown safety (low toxicity) with some promising preliminary results.…”
Section: Family Herpesviridae: Herpes Simplex Virus 1 (Hsv)mentioning
confidence: 99%
“…Shedding of crHAdVs from injection sites and patient excretions, although not always reported, has been observed in several (pre) clinical trials, and increases with higher doses and systemic administration. 49,[58][59][60][61][62][63][64] Shedding of HAdV vectors could result in homologous recombination between AdVs of the same subgroup, which occurs with high efficiency during growth in co-infected cultured cells, and there is evidence of recombination events in humans as well. [65][66][67] Theoretically, homologous recombination between wildtype AdVs and recombinant crHAdVs could lead to new wildtype AdVs that e.g.…”
Section: Family Herpesviridae: Herpes Simplex Virus 1 (Hsv)mentioning
confidence: 99%
“…Further studies showed that ORCA-010 kills cancer cells more effectively than primary nonmalignant cells. Despite the enhanced potency, ORCA-010 was as selective as Ad5-D24RGD, which was shown to be safe for use in humans up to 3 · 10 ORCA-010 ANTITUMOR ACTIVITY IN PRECLINICAL MODELSviral particles (Kimball et al, 2010;Pesonen et al, 2012;Clemens Dirven, personal communication). Moreover, intratumoral injection of ORCA-010 in human prostate, ovarian, and lung cancer tumors xenografted in immunedeficient mice resulted in significant inhibition of tumor growth and prolonged survival.…”
Section: Orca-010 Replicates In Pc-3 Tumor Xenograftsmentioning
confidence: 99%